FORMATION OF CREATIVISM IN THE STUDENT YOUTH OF NEW UZBEKISTAN THROUGH BIONICS (ON THE EXAMPLE OF THE KHOREZM OASIS) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the potential of bionics as a multidisciplinary approach to stimulate and develop creativism among student youth in the context of New Uzbekistan, focusing particularly on the Khorezm oasis. It examines how principles derived from nature-inspired design and innovation can be integrated into education to foster original thinking, ecological awareness, and technological innovation. Using Khorezm’s unique natural and historical ecosystem as a resourceful educational medium, the study proposes pedagogical strategies for embedding bionic principles into academic curricula and extracurricular activities.